Effect of Zirconia Nanofibers Structure Evolution on the Hardness and Young’s Modulus of Their Mats - Vyacheslav V. Rodaev (MDPI AG, 2021)
Zirconia nanofiber mats containing filaments with the average diameter of less than 100 nm were fabricated. It is found that the hardness and Young’s modulus of the mats are sensitive to the microstructure, phase composition and average diameter of the zirconia nanofibers. The hardness and Young’s modulus of the prepared zirconia nanofiber mats vary from 0.86 to 1.67 MPa and from 133 to 362 MPa, respectively, wherein an increase in hardness is accompanied by the rise in Young’s modulus.